Navigating uncertainty and competing objectives: Spring chinook salmon recovery in the upper Willamette river - Claire E. Couch; J. Rose Wallick; James T. Peterson; Bailey A. Morgan; Matthew L. Keefer; Christopher C. Caudill; Kathleen G. O’Malley; Christina A. Murphy; James S. White; Jake R. Kelley; Dalton J. Hance; Gabriel S. Hansen; et al. (Reviews in Fish Biology and Fisheries, 2026)

Giant predators, tiny pollutants: Exploring anthropogenic microparticles in the feces of white sharks (Carcharodon carcharias) - Gretchen K. Bielmyer-Fraser; Julia M. Courville; Morgan Vervaeke; Lisa A. Hoopes; Michael W. Hyatt; Brett McBride; G. Christopher Fischer; Alisa L. Newton (Environmental Pollution, 2026)

Leveraging Pharmacy Education through a Train-the-Trainer Model to Enhance Breast Cancer Literacy in Rural Communities - Christopher L. Farrell; Melanie R. Ginzburg; Morgan B. Enlow; Missouri M. Jenkins; Alexus N. Hames; Cayla R. Adams; Marlana A. Roberts; Hillary E. Stamps; Natalie A. Paxton; Courtney N. Addison; Austin Y. Shull (Journal of Cancer Education, 2026)
Rural versus urban communities experience disproportionate challenges in breast cancer outcomes, with higher breast cancer mortality and later stage disease presentation, despite similar diagnosis rates. These disparities are driven by structural barriers, including rural hospital closures, transportation difficulties, and limited access to oncology specialists. This study evaluated a train-the-trainer program designed to equip PharmD students located at a pharmacy school in a rural county in South Carolina with breast cancer education training, leveraging the pharmacists’ position as accessible healthcare professionals in rural communities. Training focused on breast cancer risk factors, prevention, screening, genetics, staging, and treatment options. Effectiveness was measured through pre- and post-workshop confidence surveys and knowledge assessments. Results showed significant improvement in student confidence across educational domains, with average scores increasing from 6.30 to 8.59 ( p < 0.0001). Understanding of screening guidelines (mean difference: 4.30; p -value: < .0001) and target therapy options showed the greatest improvement (mean difference: 3.65; p -value: < .0001), while knowledge of BRCA gene inheritance showed the smallest change (mean difference: 0.369; p -value: ns), suggesting some pre-existing awareness but limited understanding of its clinical applications. Overall, this pilot program demonstrates how pharmacy education can address healthcare disparities in rural communities. By preparing pharmacists to deliver accurate breast cancer education and to increase rural patient agency, this model creates a sustainable approach to improving health literacy in medically underserved areas. Future research could further expand this model to include diverse healthcare professionals and incorporate long-term impact assessments in community settings.

Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

HPAI drives a fourfold increase in adult gannet mortality which requires two decades recovery time - Jude V. Lane; Jason Matthiopoulos; David Astins; Ian Cleasby; Keith C. Hamer; Kirsty A. Franklin; Ruth Jeavons; Liam P. Langley; Aly McCluskie; Greg Morgan; Lisa Morgan; Christopher J. Pollock; et al. (Biological Conservation, 2026)

A Framework to Investigate the Effects of Observation Error on Neural Network Predictions of Fish Age - Derek W. Chamberlin; Thomas E. Helser; John D. Brogan; Irina M. Benson; Jason Conner; Andrew T. Chin; Christopher M. Gburski; Mary Elizabeth Matta; Julie A. Pearce; Kali R. Stone; Todd T. TenBrink; Morgan B. Arrington (Fish and Fisheries, 2026)
Technological innovations for predicting fish age represent a paradigm shift from conventional age estimation methods used in fisheries science. Recently developed secondary methods rely on models trained on conventional age estimates, derived from subjective interpretation of growth patterns and a biological property of the fish to predict age. Hence, quantifying the error that propagates from these models and the conventional age estimates on which they are trained is critical to fully account for uncertainty in predicted ages used in fisheries stock assessments. We review the development of three secondary age prediction methods: image analysis, epigenetics and Fourier transform near‐infrared spectroscopy (FT‐NIRS); the use of artificial intelligence (AI) within each method; and present an approach to examine the effects of ageing error on AI age prediction models. As a case study, we conducted an empirical study, coupled with simulation, to quantify the effects of ageing error on the performance of a multimodal convolutional neural network (MMCNN) model used to predict eastern Bering Sea walleye pollock ( Gadus chalcogrammus ) ages from otoliths analysed using FT‐NIRS. Results indicated repeatability of predicted ages was high between instrument operators, while adding ageing error resulted in a slight decrease in model performance from R 2 = 0.92 and CV = 7.6% to R 2 = 0.87 and CV = 10.2% on test datasets. Our results also suggest the MMCNN model is robust to noise in calibration age data and model performance may be better than performance metrics indicate when the model is evaluated against data with increased error.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Variable pH habitats could help prepare stone crabs for coastal acidification - Philip M. Gravinese; Hannah E. Craft; Alex Douwes; Gretchen S. Faraci; Morgan L. Jarrett; Shelby A. Perry; Chloe E. Potts; Emma C. Rosser; Abigail L. Smith; Alexis R. Trevillian; Christopher Moore; Kimberly K. Yates (Marine Biology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Shortleaf Pine (Pinus echinata): Management Challenges, Knowledge Gaps, and Opportunities for an Unsung Species - Benjamin O. Knapp; Jacob Fraser; Joanne Baggs; Vikram E. Chhatre; David Clabo; Connor D. Crouch; Daniel C. Dey; Shaik M. Hossain; Steven B. Jack; John M. Kabrick; Kathryn R. Kidd; Steven McNulty; et al. (Journal of Forestry, 2026)
Shortleaf pine has the broadest range of the southern pine species, occurring in 22 states and extending north into New Jersey, Pennsylvania, and New York (Staten Island). Shortleaf pine has been understudied compared to loblolly pine and longleaf pine, typically favored for timber production and conservation value, respectively. The extensive range of shortleaf pine contributes to a high degree of variability within and among its ecosystems and contributes to the need to understand regional context in considering its ecology and management. The goal of this paper is to review and synthesize the state-of-knowledge on shortleaf pine ecosystems, emphasizing the importance of variation across its range in identifying management challenges and opportunities. We discuss the variation in growing conditions that occur across the geographic range, shortleaf pine natural community groups, and contemporary shortleaf pine forest types that occur on the landscape. We provide a review of the state-of-knowledge for topics related to shortleaf pine management, including its fire ecology, genetic considerations, economics, and others. Finally, we synthesize these into key considerations and highlight regionally specific management challenges and opportunities.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Transportation in net-zero emissions futures: Insights from the EMF-37 model intercomparison study - Christopher Hoehne; Matteo Muratori; John Bistline; Carol Lenox; David L. McCollum; Morgan Browning; Kara Podkaminer; Robert H. Beach; Robbie Orvis; Shiqi Ou; Page Kyle; Sharyn Lie; et al. (Energy and Climate Change, 2025)

Policy implications of net-zero emissions: A multi-model analysis of United States emissions and energy system impacts - John E.T. Bistline; Matthew Binsted; Geoffrey Blanford; Gale Boyd; Morgan Browning; Yongxia Cai; Jae Edmonds; Allen A. Fawcett; Jay Fuhrman; Ruying Gao; Chioke Harris; Christopher Hoehne; et al. (Energy and Climate Change, 2025)

Best practices for producing actionable knowledge to inform fisheries management and conservation - Cosette Arseneault-Deraps; Raegan Davis; M. E. Cole MacLeod; Erin Wilson; Ben Aubrey; Alyssa Goodenough; Jamie C. Madden; Kevin A. Adeli; Christopher Cvitanovic; Nathan Young; Julie M. Hinderer; Elizabeth A. Nyboer; et al. (Environmental Biology of Fishes, 2025)

Effects of elevated nutrient supply on litter decomposition are robust to impacts of mammalian herbivores across diverse grasslands - Adrienne B. Keller; Elizabeth T. Borer; Christopher R. Buyarski; Elsa E. Cleland; Allison Gill; Andrew S. MacDougall; Joslin L. Moore; John W. Morgan; Rebecca L. McCulley; Anita C. Risch; Eric W. Seabloom; Justin Wright; et al. (Oecologia, 2025)
Litter decomposition is one of the largest carbon (C) fluxes in terrestrial ecosystems and links aboveground biomass to soil C pools. In grasslands, decomposition drivers have received substantial attention but the role of grassland herbivores in influencing decay rates is often ignored despite their potentially large effects on standing biomass and nutrient cycling. Recent work has demonstrated that nutrient addition increases early-stage decay and suppresses late-stage decay. Mammalian herbivores can mediate the effects of nutrient supply on biomass, suggesting herbivores may alter the effects of nutrients on decomposition, though this is largely unknown. We examined how herbivory mediates the effects of nutrient supply on long-term decomposition across 19 grassland sites of the Nutrient Network distributed experiment. At each site, a full-factorial experiment of combined nitrogen (N), phosphorus (P), and micronutrient (K) enrichment (‘control’ or ‘ + NPK’) and mammalian herbivore (> ~ 50 g) exclusion (‘unfenced’ or ‘fenced’) was carried out in a randomized block design. We hypothesized that nutrient effects on litter decomposition would be strongest where herbivores caused the greatest reductions in aboveground plant biomass (i.e., at sites with more intense herbivory). After accounting for wide variation in decomposition rates across sites, we found that, within sites, elevated nutrients increased early-stage decay and suppressed late-stage decay. In contrast, neither herbivore exclusion (i.e., fencing) nor site level changes in aboveground biomass due to herbivory altered the nutrient effects on decomposition rates. Across grasslands, our results indicate that elevated nutrient supply modifies litter decomposition rates independent of herbivore impacts.

Canopy gap edge effects on overstory sap flux in a temperate mixed-hardwood forest - Morgan L. Arteman; Jodi A. Forrester; A․Christopher Oishi; Tara L. Keyser (Agricultural and Forest Meteorology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Factors affecting the spatial and temporal distribution of biofouling communities on Atlantic salmon ( Salmo salar ) farms: insights from the Broughton Archipelago, British Columbia, Canada - Devan L. Johnson; Christopher M. Pearce; Mark S. Flaherty; Laura L. E. Cowen; Morgan J. Black; Sandra V. Worst; Raquel A. Greiter Loerzer; Kaitlin C. Guitard; Matthew McGoveran; Bogdan Vornicu (Biofouling, 2025)

Corrigendum to “BCL-3 loss sensitises colorectal cancer cells to DNA damage by targeting homologous recombination” [DNA Repair 115 (2022) 103331] - Christopher Parker; Adam C. Chambers; Dustin J. Flanagan; Jasmine Wing Yu Ho; Tracey J. Collard; Greg Ngo; Duncan M. Baird; Penny Timms; Rhys G. Morgan; Owen J. Sansom; Ann C. Williams (DNA Repair, 2025)

Equity implications of net-zero emissions: A multi-model analysis of energy expenditures across income classes under economy-wide deep decarbonization policies - John Bistline; Chikara Onda; Morgan Browning; Johannes Emmerling; Gokul Iyer; Megan Mahajan; Jim McFarland; Haewon McJeon; Robbie Orvis; Francisco Ralston Fonseca; Christopher Roney; Noah Sandoval; et al. (Energy and Climate Change, 2024)

Gray box modeling of temperature dynamics and power consumption in a swine barn - Rawisha Serasinghe; Troye Sas-Wright; Sreenand Sreedevi; Eric Romich; Morgan Hayes; Christopher Zoller; Jordan D. Clark (Computers and Electronics in Agriculture, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The CRISM investigation in Mars orbit: Overview, history, and delivered data products - Frank P. Seelos; Kimberly D. Seelos; Scott L. Murchie; M. Alexandra Matiella Novak; Christopher D. Hash; M. Frank Morgan; Raymond E. Arvidson; John Aiello; Jean-Pierre Bibring; Janice L. Bishop; John D. Boldt; Ariana R. Boyd; et al. (Icarus, 2024)

Corrigendum to “An improved model for the population dynamics of cattle gastrointestinal nematodes on pasture: Parameterisation and field validation for Ostertagia ostertagi and Cooperia oncophora in Northern Temperate zones” [Vet. Parasitol. 310 (2022) 109777] - Tong Wang; Hannah Rose Vineer; Elizabeth Redman; Arianna Morosetti; Rebecca Chen; Christopher McFarland; Douglas D. Colwell; Eric R. Morgan; John S. Gilleard (Veterinary Parasitology, 2024)

Oncometabolite 2-hydroxyglutarate suppresses basal protein levels of DNA polymerase beta that enhances alkylating agent and PARG inhibition induced cytotoxicity - Kate M. Saville; Rasha Q. Al-Rahahleh; Aisha H. Siddiqui; Morgan E. Andrews; Wynand P. Roos; Christopher A. Koczor; Joel F. Andrews; Faisal Hayat; Marie E. Migaud; Robert W. Sobol (DNA Repair, 2024)

Ecomorphodynamics of oyster reefs and their influence on oyster reef morphology - Francesca Roncolato; Thomas E. Fellowes; Stephanie Duce; Carolina Mora; Oskar Johansson; Indiana Strachan; Ana B. Bugnot; Katherine Erickson; Will Figueira; Paul E. Gribben; Christopher Pine; Bree Morgan; et al. (Geomorphology, 2024)

Forging just ecologies: 25 years of urban long-term ecological research collaboration - Morgan Grove; Steward Pickett; Christopher G. Boone; Geoffrey L. Buckley; Pippin Anderson; Fushcia-Ann Hoover; Ariel E. Lugo; Elvia Meléndez-Ackerman; Tischa A. Muñoz-Erickson; Harini Nagendra; L. Kidany Selles (Ambio, 2024)
We ask how environmental justice and urban ecology have influenced one another over the past 25 years in the context of the US Long-Term Ecological Research (LTER) program and Baltimore Ecosystem Study (BES) project. BES began after environmental justice emerged through activism and scholarship in the 1980s but spans a period of increasing awareness among ecologists and environmental practitioners. The work in Baltimore provides a detailed example of how ecological research has been affected by a growing understanding of environmental justice. The shift shows how unjust environmental outcomes emerge and are reinforced over time by systemic discrimination and exclusion. We do not comprehensively review the literature on environmental justice in urban ecology but do present four brief cases from the Caribbean, Africa, and Asia, to illustrate the global relevance of the topic. The example cases demonstrate the necessity for continuous engagement with communities in addressing environmental problem solving.

The earliest evidence for a microblade adaptation in the remote, high altitude regions of the Tibetan Plateau - Yingshuai Jin; Xiaoling Zhang; Shejiang Wang; Junyi Ge; Wei He; Wa Da; Yunyao Tan; Ziyi Yang; Christopher Morgan; Xing Gao (Science China Earth Sciences, 2024)

Successful DNA amplification of DNA from non-destructive buccal swabbing in Vespertilionid and Rhinolophid bats - Morgan Hughes; Scott K Brown; Rémi Martin; Christopher H Young; Simon Maddock (Conservation Genetics Resources, 2024)
Acquiring DNA from wild bats (Mammalia: Chiroptera) is typically undertaken utilizing highly invasive (but non-lethal) sampling techniques comprising wing biopsies and occasional blood samples. While non-invasive sampling is possible through the extraction of DNA from faecal samples, it is not always possible to acquire samples from individual bats whilst conducting fieldwork, and as such, this method is primarily applicable to roost occupancy identification. Similarly, wing swabbing is liable to cross-contamination from roost mates. Here we present the first use of oral (buccal) swabbing for successful, species-resolution DNA sequencing of Vespertilionidae and Rhinolophidae in 10 bat species (nine Vespertilionidae and one Rhinolophidae) from the UK.

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

Crossflow flat solid oxide fuel cell (SOFC) semi-empirical modeling and the multi-fuel property based on a commercial 700 W stack - Junhan Cheng; Ralph Lavery; Christopher S. McCallum; Kevin Morgan; John Doran; Chunfei Wu; Kening Sun; David W. Rooney (Fuel, 2024)

Perfluoroalkyl substances (PFAS) and lead (Pb) as “cardiovascular disruptors” in 9–11-year-old children living in Syracuse, New York, United States - Brooks B. Gump; Dustin T. Hill; Morgan Robinson; Kurunthachalam Kannan; Kevin Heffernan; Nader H. Atallah-Yunes; Lynn Brann; Patrick J. Parsons; Christopher D. Palmer; James A. MacKenzie; Jackie M. Goodrich; Kestutis Bendinskas (Environmental Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Organic matter sulfurization and organic carbon burial in the Mesoproterozoic - Morgan Reed Raven; Peter W. Crockford; Malcolm S.W. Hodgskiss; Timothy W. Lyons; Christopher J. Tino; Samuel M. Webb (Geochimica et Cosmochimica Acta, 2023)

Comparison study of ductile iron produced with Martian regolith harvested iron from ionic liquids and Bosch byproduct carbon for in-situ resource utilization versus commercially available 65-45-12 ductile iron - Blake C. Stewart; Haley R. Doude; Shiraz Mujahid; Morgan B. Abney; Eric T. Fox; Jennifer E. Edmunson; Jeffrey J. Mehan; Christopher R. Henry; Phillip B. Hall; Haitham El Kadiri; Hongjoo Rhee (Advances in Space Research, 2023)

Towards a whole‐system framework for wildfire monitoring using Earth observations - Morgan A. Crowley; Christopher A. Stockdale; Joshua M. Johnston; Michael A. Wulder; Tianjia Liu; Jessica L. McCarty; Jesse T. Rieb; Jeffrey A. Cardille; Joanne C. White (Global Change Biology, 2023)
Fire seasons have become increasingly variable and extreme due to changing climatological, ecological, and social conditions. Earth observation data are critical for monitoring fires and their impacts. Herein, we present a whole‐system framework for identifying and synthesizing fire monitoring objectives and data needs throughout the life cycle of a fire event. The four stages of fire monitoring using Earth observation data include the following: (1) pre‐fire vegetation inventories, (2) active‐fire monitoring, (3) post‐fire assessment, and (4) multi‐scale synthesis. We identify the challenges and opportunities associated with current approaches to fire monitoring, highlighting four case studies from North American boreal, montane, and grassland ecosystems. While the case studies are localized to these ecosystems and regional contexts, they provide insights for others experiencing similar monitoring challenges worldwide. The field of remote sensing is experiencing a rapid proliferation of new data sources, providing observations that can inform all aspects of our fire monitoring framework; however, significant challenges for meeting fire monitoring objectives remain. We identify future opportunities for data sharing and rapid co‐development of information products using cloud computing that benefits from open‐access Earth observation and other geospatial data layers.

Current street tree communities reflect race‐based housing policy and modern attempts to remedy environmental injustice - Karin T. Burghardt; Meghan L. Avolio; Dexter H. Locke; J. Morgan Grove; Nancy F. Sonti; Christopher M. Swan (Ecology, 2023)
Humans promote and inhibit other species on the urban landscape, shaping biodiversity patterns. Institutional racism may underlie the distribution of urban species by creating disproportionate resources in space and time. Here, we examine whether present‐day street tree occupancy, diversity, and composition in Baltimore, MD, USA, neighborhoods reflect their 1937 classification into grades of loan risk—from most desirable (A = green) to least desirable (D = “redlined”)—using racially discriminatory criteria. We find that neighborhoods that were redlined have consistently lower street tree α‐diversity and are nine times less likely to have large (old) trees occupying a viable planting site. Simultaneously, redlined neighborhoods were locations of recent tree planting activities, with a high occupancy rate of small (young) trees. However, the community composition of these young trees exhibited lower species turnover and reordering across neighborhoods compared to those in higher grades, due to heavy reliance on a single tree species. Overall, while the negative effects of redlining remain detectable in present‐day street tree communities, there are clear signs of recent investment. A strategy of planting diverse tree cohorts paired with investments in site rehabilitation and maintenance may be necessary if cities wish to overcome ecological feedbacks associated with legacies of environmental injustice.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Assessing neophobia and exploration while accounting for social context: an example application in scimitar-horned oryx - Katherine Mertes; Catherine A. Ressijac; Rosana N. Moraes; Lacey F. Hughey; Luisa H. Porto Alegre; Megan Horning; Tara Buk; Arielle Harwood; Lawrence Layman; Christopher Mathews; Morgan Vance; Dolores Reed; et al. (Mammalian Biology, 2022)
Spatial neophobia and exploration are often assessed in nonhuman animals by measuring behavioral responses to novel environments. These traits may especially affect the performance of individuals translocated to novel environments for conservation purposes. Here, we present methods to administer and analyze a minimally invasive novel environment test that accounts for the social context of focal individuals. We used an aerial platform to capture video footage of a captive herd of scimitar-horned oryx ( Oryx dammah ) entering an unfamiliar enclosure. We analyzed footage for seven individually identifiable oryx, scoring their behavioral responses (i.e., latency to enter the enclosure, and movement and posture after entering the enclosure) and social context (i.e., relative position and number of nearby animals). We performed a principal components analysis (PCA) to explore individual traits and responses, and used generalized linear mixed models (GLMMs) to determine the effect of individual traits and social context on individual posture and movement behaviors. Both PCA and GLMMs supported our expectation that social context affects individual behavior: high neighbor density and relative position were negatively related to individual movement, and variation in social context was positively related with head-up postures and movement. Oryx were well differentiated along two principal components that reflected (1) vigilance or caution, and (2) changing social context and age. These methods provide a framework for assessing individual responses to a novel environment in a group setting, which can inform reintroduction and wildlife management efforts, while minimizing interference with animal behavior and management operations.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Opening Doors to Training Medical Toxicology Fellows from All Residency Backgrounds - Louise Kao; Michele Burns; Christine Murphy; Evan Schwarz; Steve Aks; Kavita Babu; Gillian Beauchamp; Rana Biary; Michele Burns; Nathan Charlton; Cathleen Clancy; Jonathan Ford; et al. (Journal of Medical Toxicology, 2022)

Performance of Multiple-Batch Approaches to Pharmacokinetic Bioequivalence Testing for Orally Inhaled Drug Products with Batch-to-Batch Variability - Elise Burmeister Getz; Kevin J. Carroll; J. David Christopher; Beth Morgan; Scott Haughie; Alessandro Cavecchi; Christopher Wiggenhorn; Hayden Beresford; Helen Strickland; Svetlana Lyapustina (AAPS PharmSciTech, 2021)
Batch-to-batch pharmacokinetic (PK) variability of orally inhaled drug products has been documented and can render single-batch PK bioequivalence (BE) studies unreliable; results from one batch may not be consistent with a repeated study using a different batch, yet the goal of PK BE is to deliver a product comparison that is interpretable beyond the specific batches used in the study. We characterized four multiple-batch PK BE approaches to improve outcome reliability without increasing the number of clinical study participants. Three approaches include multiple batches directly in the PK BE study with batch identity either excluded from the statistical model (“Superbatch”) or included as a fixed or random effect (“Fixed Batch Effect,” “Random Batch Effect”). A fourth approach uses a bio-predictive in vitro test to screen candidate batches, bringing the median batch of each product into the PK BE study (“Targeted Batch”). Three of these approaches (Fixed Batch Effect, Superbatch, Targeted Batch) continue the single-batch PK BE convention in which uncertainty in the Test/Reference ratio estimate due to batch sampling is omitted from the Test/Reference confidence interval. All three of these approaches provided higher power to correctly identify true bioequivalence than the standard single-batch approach with no increase in clinical burden. False equivalence (type I) error was inflated above the expected 5% level, but multiple batches controlled type I error better than a single batch. The Random Batch Effect approach restored 5% type I error, but had low power for small ( e.g. ,

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

To EBFM or not to EBFM? that is not the question - Mandy Karnauskas; John F. Walter; Christopher R. Kelble; Matthew McPherson; Skyler R. Sagarese; J. Kevin Craig; Adyan Rios; William J. Harford; Seann Regan; Steven D. Giordano; Morgan Kilgour (Fish and Fisheries, 2021)
The ecosystem‐based fisheries management (EBFM) framework has a solid theoretical justification and has been embraced in principle by many regions; yet, systematic implementation remains a challenge. In regions with strong governance, single‐species stock assessment and management has been successful in ending overfishing and maintaining stocks near levels that produce maximum catches. However, considering species in isolation and recognizing a limited set of management objectives leads to systemic inefficiencies, incentivizes waste and generates unintended consequences. To avoid undesirable outcomes, human values and needs must be positioned at the forefront of management, system‐level objectives must be identified, and management actions must be systematically evaluated to ensure they are contributing to those larger objectives. Such processes, when implemented transparently, will lead to reduced conflict and improved stakeholder support for governance and should greatly facilitate long‐term management. We argue here that, regardless of the management framework adopted, we inherently manage at the ecosystem level—albeit sometimes “blindly”—and that increased attention to ecosystem objectives and trade‐offs will improve management outcomes.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Tricyclic antipsychotics promote adipogenic gene expression to potentiate preadipocyte differentiation in vitro - Christopher M. Cottingham; Taylor Patrick; Morgan A. Richards; Kirkland D. Blackburn (Human Cell, 2020)

Evaluation of the Sensitivity and Robustness of Modified Chi-Square Ratio Statistic for Cascade Impactor Equivalence Testing Through Monte Carlo Simulations - Abhinav Kurumaddali; David Christopher; Helen Strickland; Beth Morgan; Christopher Wiggenhorn; Stephen Stein; Svetlana Lyapustina; Günther Hochhaus (AAPS PharmSciTech, 2020)

Performance of the Population Bioequivalence (PBE) Statistical Test with Impactor Sized Mass Data - Stephanie Chen; Beth Morgan; Hayden Beresford; Elise Burmeister Getz; David Christopher; Göran Långström; Helen Strickland; Christopher Wiggenhorn; Svetlana Lyapustina (AAPS PharmSciTech, 2019)

The effects of mitragynine and morphine on schedule-controlled responding and antinociception in rats - Takato Hiranita; Francisco Leon; Jasmine S. Felix; Luis F. Restrepo; Morgan E. Reeves; Anna E. Pennington; Samuel Obeng; Bonnie A. Avery; Christopher R. McCurdy; Lance R. McMahon; Jenny L. Wilkerson (Psychopharmacology, 2019)

Cascade Impactor Equivalence Testing: Comparison of the Performance of the Modified Chi-Square Ratio Statistic (mCSRS) with the Original CSRS and EMA’s Average Bioequivalence Approach - Abhinav Kurumaddali; David Christopher; Dennis Sandell; Helen Strickland; Beth Morgan; Juergen Bulitta; Christopher Wiggenhorn; Stephen Stein; Svetlana Lyapustina; Günther Hochhaus (AAPS PharmSciTech, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Performance of the Population Bioequivalence (PBE) Statistical Test Using an IPAC-RS Database of Delivered Dose from Metered Dose Inhalers - Beth Morgan; Stephanie Chen; David Christopher; Göran Långström; Christopher Wiggenhorn; Elise Burmeister Getz; Hayden Beresford; Thomas Hoffelder; Daniela Acerbi; Stephen Andrews; Mark Berry; Monisha Dey; et al. (AAPS PharmSciTech, 2018)

Localised hydrodynamics influence vulnerability of coral communities to environmental disturbances - George Shedrawi; James L. Falter; Kim J. Friedman; Ryan J. Lowe; Morgan S. Pratchett; Christopher J. Simpson; Conrad W. Speed; Shaun K. Wilson; Zhenlin Zhang (Coral Reefs, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Heat Survival and Phenotype Microarray Profiling of Salmonella Typhimurium Mutants - Turki M. Dawoud; Anita Khatiwara; Si Hong Park; Morgan L. Davis; Christopher A. Baker; Steven C. Ricke; Young Min Kwon (Current Microbiology, 2017)

A test of the migration-modulation hypothesis in a non-passerine Neotropical migrant, the Blue-winged Teal Anas discors - C. Morgan Wilson; Christopher G. Sims; Stephan J. Schoech; Sarah K. Peltier; Zachary L. Robinson (Journal of Ornithology, 2017)

Fish as proxies of ecological and environmental change - Christopher Izzo; Zoë A. Doubleday; Gretchen L. Grammer; Kayla L. Gilmore; Heidi K. Alleway; Thomas C. Barnes; Morgan C. F. Disspain; Ana Judith Giraldo; Nastaran Mazloumi; Bronwyn M. Gillanders (Reviews in Fish Biology and Fisheries, 2016)

Toward an Understanding of Citywide Urban Environmental Governance: An Examination of Stewardship Networks in Baltimore and Seattle - Michele Romolini; J. Morgan Grove; Curtis L. Ventriss; Christopher J. Koliba; Daniel H. Krymkowski (Environmental Management, 2016)

A framework for understanding climate change impacts on coral reef social–ecological systems - Joshua Eli Cinner; Morgan Stuart Pratchett; Nicholas Anthony James Graham; Vanessa Messmer; Mariana Menezes Prata Bezerra Fuentes; Tracy Ainsworth; Natalie Ban; Line Kolind Bay; Jessica Blythe; Delphine Dissard; Simon Dunn; Louisa Evans; et al. (Regional Environmental Change, 2016)

Life history strategies of the Scotia Sea icefish, Chaenocephalus aceratus, along the Southern Scotia Ridge - Emilio Riginella; Carlotta Mazzoldi; Julian Ashford; Christopher D. Jones; Christina Morgan; Mario La Mesa (Polar Biology, 2016)

In Vitro Testing for Orally Inhaled Products: Developments in Science-Based Regulatory Approaches - Ben Forbes; Per Bäckman; David Christopher; Myrna Dolovich; Bing V. Li; Beth Morgan (The AAPS Journal, 2015)

Mitochondrial data are not suitable for resolving placental mammal phylogeny - Claire C. Morgan; Christopher J. Creevey; Mary J. O’Connell (Mammalian Genome, 2014)

Linking Indices for Biodiversity Monitoring to Extinction Risk Theory - MICHAEL A. MCCARTHY; ALANA L. MOORE; JOCHEN KRAUSS; JOHN W. MORGAN; CHRISTOPHER F. CLEMENTS (Conservation Biology, 2014)
Biodiversity indices often combine data from different species when used in monitoring programs. Heuristic properties can suggest preferred indices, but we lack objective ways to discriminate between indices with similar heuristics. Biodiversity indices can be evaluated by determining how well they reflect management objectives that a monitoring program aims to support. For example, the Convention on Biological Diversity requires reporting about extinction rates, so simple indices that reflect extinction risk would be valuable. We developed 3 biodiversity indices that are based on simple models of population viability that relate extinction risk to abundance. We based the first index on the geometric mean abundance of species and the second on a more general power mean. In a third index, we integrated the geometric mean abundance and trend. These indices require the same data as previous indices, but they also relate directly to extinction risk. Field data for butterflies and woodland plants and experimental studies of protozoan communities show that the indices correlate with local extinction rates. Applying the index based on the geometric mean to global data on changes in avian abundance suggested that the average extinction probability of birds has increased approximately 1% from 1970 to 2009. Conectando Índices para el Monitoreo de la Biodiversidad con la Teoría de Riesgo de Extinción

On-Command Drug Release from Nanochains Inhibits Growth of Breast Tumors - Pubudu M. Peiris; Morgan Tam; Peter Vicente; Aaron Abramowski; Randall Toy; Lisa Bauer; Aaron Mayer; Jenna Pansky; Elizabeth Doolittle; Samantha Tucci; Erik Schmidt; Christopher Shoup; et al. (Pharmaceutical Research, 2014)

Foraging in corallivorous butterflyfish varies with wave exposure - Mae M. Noble; Morgan S. Pratchett; Darren J. Coker; Christopher Cvitanovic; Christopher J. Fulton (Coral Reefs, 2014)

Population genetics of Blanding’s turtle (Emys blandingii) in the midwestern United States - Arun Sethuraman; Suzanne E. McGaugh; Morgan L. Becker; Christopher H. Chandler; James L. Christiansen; Sue Hayden; Andrea LeClere; Jennifer Monson-Miller; Erin M. Myers; Ryan T. Paitz; Jeanine M. Refsnider; Terry J. VanDeWalle; et al. (Conservation Genetics, 2014)

Impacts of inundation and drought on eukaryote biodiversity in semi‐arid floodplain soils - Darren S. Baldwin; Matthew J. Colloff; Gavin N. Rees; Anthony A. Chariton; Garth O. Watson; Leon N. Court; Diana M. Hartley; Matthew j. Morgan; Andrew J. King; Jessica S. Wilson; Michael Hodda; Christopher M. Hardy (Molecular Ecology, 2013)
Floodplain ecosystems are characterized by alternating wet and dry phases and periodic inundation defines their ecological character. Climate change, river regulation and the construction of levees have substantially altered natural flooding and drying regimes worldwide with uncertain effects on key biotic groups. In southern A ustralia, we hypothesized that soil eukaryotic communities in climate change affected areas of a semi‐arid floodplain would transition towards comprising mainly dry‐soil specialist species with increasing drought severity. Here, we used 18S r RNA amplicon pyrosequencing to measure the eukaryote community composition in soils that had been depleted of water to varying degrees to confirm that reproducible transitional changes occur in eukaryotic biodiversity on this floodplain. Interflood community structures (3 years post‐flood) were dominated by persistent rather than either aquatic or dry‐specialist organisms. Only 2% of taxa were unique to dry locations by 8 years post‐flood, and 10% were restricted to wet locations (inundated a year to 2 weeks post‐flood). Almost half (48%) of the total soil biota were detected in both these environments. The discovery of a large suite of organisms able to survive nearly a decade of drought, and up to a year submerged supports the concept of inherent resilience of Australian semi‐arid floodplain soil communities under increasing pressure from climatic induced changes in water availability.

Gastric cancer incidence estimation in a resource-limited nation: use of endoscopy registry methodology - Ricardo L. Dominguez; Seth D. Crockett; Jennifer L. Lund; Lia P. Suazo; Paris Heidt; Christopher Martin; Douglas R. Morgan (Cancer Causes & Control, 2013)

The potential role of an unregulated coastal anthropogenic activity in facilitating the spread of a non-indigenous biofoulant - Eilir Hedd Morgan; Christopher Alan Richardson (Biofouling, 2012)

New evidence for extreme and persistent terminal medieval drought in California’s Sierra Nevada - Christopher Morgan; Monique M. Pomerleau (Journal of Paleolimnology, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Ethylene vinyl acetate intravaginal rings for the simultaneous delivery of the antiretroviral UC781 and contraceptive levonorgestrel - Andrew Loxley; Mark Mitchnick; Onajite Okoh; Jason McConnell; Laurie Goldman; Christopher Morgan; Meredith Clark; David R. Friend (Drug Delivery and Translational Research, 2011)

Landscape, vegetation characteristics, and group identity in an urban and suburban watershed: why the 60s matter - Christopher G. Boone; Mary L. Cadenasso; J. Morgan Grove; Kirsten Schwarz; Geoffrey L. Buckley (Urban Ecosystems, 2010)

Challenges to Educating the Next Generation of Wildland Fire Professionals in the United States - Leda N. Kobziar; Monique E. Rocca; Christopher A. Dicus; Chad Hoffman; Neil Sugihara; Andrea E. Thode; J. Morgan Varner; Penelope Morgan (Journal of Forestry, 2009)
Over the last 20 years, the duties of US fire professionals have become more complex and risk laden because of fuel load accumulation, climate change, and the increasing wildland-urban interface. Incorporation of fire use and ecological principles into fire management policies has further expanded the range of expertise and knowledge required of fire professionals. The educational and training systems that produce these professionals, however, have been slow to organize an updated and coordinated approach to preparing future practitioners. Consequently, aspiring fire professionals face numerous challenges related to scheduling conflicts, limited higher education programs in fire science, lack of coordination between fire training and higher education entities, and the overall difficulty of obtaining education and training without sacrificing experience. Here, we address these and other challenges with potential solutions and outline the first steps toward their implementation. We organize the necessary aspects of professional fire preparation into a representative model: a fire professional development triangle comprised of education, training, and experience. For each of these aspects, we suggest changes that can be made by employers, educators, and nongovernmental organizations to provide a more streamlined mechanism for preparing the next generation of wildland fire professionals in the United States.

Comparison of 50- and 100-g l-tryptophan depletion and loading formulations for altering 5-HT synthesis: pharmacokinetics, side effects, and mood states - Donald M. Dougherty; Dawn M. Marsh-Richard; Charles W. Mathias; Ashley J. Hood; Merideth A. Addicott; F. Gerard Moeller; Christopher J. Morgan; Abdulla A.-B. Badawy (Psychopharmacology, 2008)

Adverse effects from environmental mercury loads on breeding common loons - David C. Evers; Lucas J. Savoy; Christopher R. DeSorbo; David E. Yates; William Hanson; Kate M. Taylor; Lori S. Siegel; John H. Cooley; Michael S. Bank; Andrew Major; Kenneth Munney; Barry F. Mower; et al. (Ecotoxicology, 2008)

Product quality research institute evaluation of cascade impactor profiles of pharmaceutical aerosols, part 3: Final report on a statistical procedure for determining equivalence - David Christopher; Wallace Adams; Anthony Amann; Craig Bertha; Peter R. Byron; William Doub; Craig Dunbar; Walter Hauck; Svetlana Lyapustina; Jolyon Mitchell; Beth Morgan; Steve Nichols; et al. (AAPS PharmSciTech, 2007)

Microbial life in Champagne Pool, a geothermal spring in Waiotapu, New Zealand - Adrian Hetzer; Hugh W. Morgan; Ian R. McDonald; Christopher J. Daughney (Extremophiles, 2007)

Product Quality Research Institute evaluation of cascade impactor profiles of pharmaceutical aerosols: Part 2—Evaluation of a method for determining equivalence - David Christopher; Wallace P. Adams; Douglas S. Lee; Beth Morgan; Ziqing Pan; Gur Jai Pal Singh; Yi Tsong; Svetlana Lyapustina (AAPS PharmSciTech, 2007)

Product Quality Research Institute evaluation of cascade impactor profiles of pharmaceutical aerosols, part 1: Background for a statistical method - Wallace P. Adams; David Christopher; Douglas S. Lee; Beth Morgan; Ziqing Pan; Gur Jai Pal Singh; Yi Tsong; Svetlana Lyapustina (AAPS PharmSciTech, 2007)

Discrete-trials heroin self-administration produces sensitization to the reinforcing effects of cocaine in rats - Sara J. Ward; Christopher Läck; Drake Morgan; David C. S. Roberts (Psychopharmacology, 2006)

Inbreeding, outbreeding and environmental effects on genetic diversity in 46 walleye ( Sander vitreus ) populations - CHRISTOPHER J. CENA; GEORGE E. MORGAN; MICHAEL D. MALETTE; DANIEL D. HEATH (Molecular Ecology, 2006)
Genetic diversity is recognized as an important population attribute for both conservation and evolutionary purposes; however, the functional relationships between the environment, genetic diversity, and fitness‐related traits are poorly understood. We examined relationships between selected lake parameters and population genetic diversity measures in 46 walleye ( Sander vitreus ) populations across the province of Ontario, Canada, and then tested for relationships between six life history traits (in three categories: growth, reproductive investment, and mortality) that are closely related to fitness, and genetic diversity measures (heterozygosity, d 2 , and Wright's inbreeding coefficient). Positive relationships were observed between lake surface area, growing degree days, number of species, and hatchery supplementation versus genetic diversity. Walleye early growth rate was the only life history trait significantly correlated with population heterozygosity in both males and females. The relationship between F IS and male early growth rate was negative and significant ( P 0.01) and marginally nonsignificant for females ( P = 0.06), consistent with inbreeding depression effects. Only one significant relationship was observed for d 2 : female early growth rate ( P 0.05). Stepwise regression models showed that surface area and heterozygosity had a significant effect on female early growth rate, while hatchery supplementation, surface area and heterozygosity had a significant effect on male early growth rate. The strong relationship between lake parameters, such as surface area, and hatchery supplementation, versus genetic diversity suggests inbreeding and outbreeding in some of the populations; however, the weak relationships between genetic diversity and life history traits indicate that inbreeding and outbreeding depression are not yet seriously impacting Ontario walleye populations.

Volunteer Environmental Monitoring and the Role of the Universities: The Case of Citizens' Environment Watch - BETH SAVAN; ALEXIS J. MORGAN; CHRISTOPHER GORE (Environmental Management, 2003)

A novel locus for Meckel-Gruber syndrome, MKS3 , maps to chromosome 8q24 - Neil Morgan; Paul Gissen; Saghira Sharif; Laura Baumber; Joan Sutherland; Deirdre Kelly; Kingi Aminu; Christopher Bennett; Geoffrey Woods; Robert Mueller; Richard Trembath; Eamonn Maher; et al. (Human Genetics, 2002)

Sensorimotor gating effects produced by repeated dopamine agonists in a paradigm favoring environmental conditioning - David Feifel; Kristianne Priebe; Elizabeth Johnstone-Miller; Christopher J. Morgan (Psychopharmacology, 2002)

The influence of exogenous peptide on β 2 -microglobulin exchange in the HLA complex: analysis in real-time - Claire L. Morgan; Anita K. Ruprai; Alejandra Solache; Mark Lowdell; Christopher P. Price; Shara B. A. Cohen; Peter Parham; J. Alejandro Madrigal; David J. Newman (Immunogenetics, 1998)